On-demand treatment of metabolic diseases by a synthetic drug-inducible exocytosis system - Yaqing Si; Minghui He; Yilin Li; Jian Jiang; Yuxuan Fan; Shuai Xue; Xinyuan Qiu; Mingqi Xie (Nature Communications)
Abstract Here, we present StimExo as a rational design strategy allowing various user-defined control signals to trigger calcium-dependent exocytosis and mediate on-demand protein secretion in cell-therapy settings. Using a modular framework incorporating inducible protein-protein interactions into an engineered bipartite activator of calcium release–activated calcium (CRAC) channels, Ca2+ influx mediated by the STIM/Orai1 machinery was flexibly adjusted to depend on different user-defined input signals. Application of StimExo to various endocrine cells enables instant secretion of therapeutic hormones upon administration of safe and patient-compliant trigger compounds. StimExo also mediated insulin exocytosis using a cell-based gene delivery strategy in vivo, accounting for real-time control of blood glucose homeostasis in male diabetic mice in response to the FDA-approved drug grazoprevir. This study achieves true “sense-and-respond” cell-based therapies and provides a platform for remote control of in vivo transgene activities using various trigger signals of interest.